Multifactorial hypercoagulable state associated with a thrombotic phenotype in phosphomannomutase-2 congenital disorder of glycosylation (PMM2-CDG): Case report and brief review of the literature. Issue 178 (June 2019) - Lefrère, Bertrand; Stepanian, Alain; Charles, Perrine; Foulon-Pinto, Geoffrey; Béranger, Nicolas; Alhenc-Gelas, Martine; Drouet, Ludovic; Siguret, Virginie
Highlights: Among PMM2-CDG patients, deep venous thrombosis of the lower limb is uncommon. Thrombinography and fibrinography results evidenced here a prothrombotic phenotype. An increased proportion of intermediate/high MM of VWF multimers was observed. Considering AT deficiency in PMM2-CDG, DOAC can be an attractive treatment option.